Historical Dictionary of Ethiopia - Shinn, David H.; Ofcansky, Thomas P. (Rowman & Littlefield Publishers, 2013)
Ethiopia is clearly one of the most important countries in Africa. First of all, with about 75 million people, it is the third most populous country in Africa. Second, it is very strategically located, in the Horn of Africa and bordering Eritrea, Sudan, Kenya, and Somalia, with some of whom it has touchy and sometimes worse relations. Yet, its capital – Addis Ababa – is the headquarters of the African Union, the prime meeting place for Africa’s leaders. So, if things went poorly in Ethiopia, this would not be good for Africa, and for a long time this was the case, with internal disruption rife, until it was literally suppressed under the strong rule of the recently deceased Meles Zenawi. The Historical Dictionary of Ethiopia, Second Edition covers the history of Ethiopia through a chronology, an introductory essay, appendixes, and an extensive bibliography. The dictionary section has several hundred cross-referenced entries on important personalities, politics, economy, foreign relations, religion, and culture. This book is an excellent access point for students, researchers, and anyone wanting to know more about Ethiopia.